The Utilization of Public Land and Environmental Management in Transmigration Settlement - Sambas Basuni (Media Konservasi, 1991)
Environmental 'problems basical& start with lack of awareness on good environment. I f we rela this problem with land ownership, the public land usual& has its own problem due to lack ofpersonal responsibiliiy in managing the public land Thir paper attempts to present some ideas in environmental management in transmigration settlement. In general, land in transmigration settlement can be categorized into two major usages, ic, production area and non-pabction area. The nan-productionareas occasiunally ean cause environmentalproblems in nansmig7ation settlement.